2017
DOI: 10.1002/macp.201700235
|View full text |Cite
|
Sign up to set email alerts
|

Strong Memory Effect of Metastable β Form Trans‐1,4‐Polyisoprene above Equilibrium Melting Temperature

Abstract: The memory effect of metastable β form crystals of trans‐1,4‐polyisoprene (TPI) is investigated with its thermodynamically stable α‐TPI as reference. Unexpectedly, β‐TPI exhibits a stronger memory effect over α‐TPI. The memory temperature of β‐TPI can be 20 °C higher than its equilibrium melting point (78 °C), while α‐TPI has lost memory below the equilibrium melting point (87 °C). Moreover, the ordered structures in β‐TPI memorized melt accelerate spherulite growth, and the growth rate depends on melting time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Scarce literature observations have reported faster crystal growth rate upon recrystallization from nonisotropic melts. 177 Since in the majority of cases the possible effect of melt memory on the growth process is neglected, due to the overwhelming impact on nucleation, it seems worth to reconsider this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Scarce literature observations have reported faster crystal growth rate upon recrystallization from nonisotropic melts. 177 Since in the majority of cases the possible effect of melt memory on the growth process is neglected, due to the overwhelming impact on nucleation, it seems worth to reconsider this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of two amorphous phases has been directly demonstrated by Rastogi et al during pressing poly­(4-methyl-1-pentene), , although LLPS has not been observed between these two liquids. Studies on memory effects of various polymers also support the existence of different liquids, although their structures are unknown yet. For instance, heating β and α forms of trans -1,4-polyisoprene (TPI) above their T m 0 , the melt of β crystals shows a strong memory effect to trigger nucleation of α (not β) crystal after cooling while melting the α crystal loses memory completely . Different memory effects are also observed in melting iPP mesophase and α form. , Different crystal forms melt into different liquids resembling the correlation between the two liquids and two glasses of water.…”
Section: “Two-step” Nucleation Modelsmentioning
confidence: 99%
“…134−136 For instance, heating β and α forms of trans-1,4-polyisoprene (TPI) above their T m 0 , the melt of β crystals shows a strong memory effect to trigger nucleation of α (not β) crystal after cooling while melting the α crystal loses memory completely. 136 Different memory effects are also observed in melting iPP mesophase and α form. 134,135 Different crystal forms melt into different liquids resembling the correlation between the two liquids and two glasses of water.…”
Section: "Two-step" Nucleation Modelsmentioning
confidence: 99%
“…However, many studies also illustrated that melt memory still exists after the crystal fragments are completely melted at higher temperatures ( T s > T m,end ) for various polymers including isotactic polypropylene and propene/ethylene random copolymers, segmented thermoplastic polyurethane elastomers (TPUs), poly­(butylene succinate) (PBS) homopolymer and poly­(butylene succinate- ran -butylene azelate) copolyesters, poly­(ε-caprolactone) (PCL), ,, ethylene/1-hexene random copolymers, 1-butene/ethylene random copolymers (PB1- ran -PE), and poly­( l -lactide)-based block copolymers . In some reports, a strong memory effect has been found even beyond the equilibrium melt temperature ( T m 0 ) of polymers ( T s > T m 0 ) in a few homopolymers like trans -1,4-polyisoprene and some copolymers containing ethylene/1-butene random copolymers analogous to hydrogenated polybutadienes (HPBDs) , and butene-1/norbornene (NBE) random copolymers . Therein, the key factor for SN in these copolymers is the melt topology complexity due to the long stable crystallizable sequence aggregation and the formation of topological constraints, i.e., loops, links, and ties in the intercrystalline regions, resulting in heterogeneous melts at temperatures above T m 0 . , Apart from this, different hypotheses for the exact nature of the melt memory effect have been suggested for specific systems, for instance, residual segmental orientations inside the pre-existing crystals, ,,, molten clusters (embryos), , residual segmental interactions, an inhomogeneous intermediate metastable melt state, ,,, a state with weak liquid–liquid phase separation, and heterogeneous distribution in melt entanglements. , …”
Section: Introductionmentioning
confidence: 99%
“…In some reports, a strong memory effect has been found even beyond the equilibrium melt temperature ( T m 0 ) of polymers ( T s > T m 0 ) in a few homopolymers like trans -1,4-polyisoprene and some copolymers containing ethylene/1-butene random copolymers analogous to hydrogenated polybutadienes (HPBDs) , and butene-1/norbornene (NBE) random copolymers . Therein, the key factor for SN in these copolymers is the melt topology complexity due to the long stable crystallizable sequence aggregation and the formation of topological constraints, i.e., loops, links, and ties in the intercrystalline regions, resulting in heterogeneous melts at temperatures above T m 0 . , Apart from this, different hypotheses for the exact nature of the melt memory effect have been suggested for specific systems, for instance, residual segmental orientations inside the pre-existing crystals, ,,, molten clusters (embryos), , residual segmental interactions, an inhomogeneous intermediate metastable melt state, ,,, a state with weak liquid–liquid phase separation, and heterogeneous distribution in melt entanglements. , …”
Section: Introductionmentioning
confidence: 99%